2020
DOI: 10.4330/wjc.v12.i6.269
|View full text |Cite
|
Sign up to set email alerts
|

Intra-procedural arrhythmia during cardiac catheterization: A systematic review of literature

Abstract: BACKGROUND Cardiac catheterization is among the most performed medical procedures in the modern era. There were sporadic reports indicating that cardiac arrhythmias are common during cardiac catheterization, and there are risks of developing serious and potentially life-threatening arrhythmias, such as sustained ventricular tachycardia (VT), ventricular fibrillation (VF) and high-grade conduction disturbances such as complete heart block (CHB), requiring immediate interventions. However, there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Isolated NSVT or PVC events often occur during right heart catheterization, that is, when the catheter tip enters the right atrium, right ventricle, pulmonary artery with a percentage of about 20%. 25 Other complication in this study was mild qualitative aortic valve regurgitation in 3.7% of the total 27 samples and no new case of tricuspid regurgitation was found from a total of 27 samples in this study shortly after the transcatheterization procesure. In a study conducted by Liu et al, (2013), it was found that the emergence of new cases of aortic valve regurgitation was 1.37% and tricuspid regurgitation was only around 0.57% of a total of 871 samples.…”
Section: Discussionmentioning
confidence: 48%
“…Isolated NSVT or PVC events often occur during right heart catheterization, that is, when the catheter tip enters the right atrium, right ventricle, pulmonary artery with a percentage of about 20%. 25 Other complication in this study was mild qualitative aortic valve regurgitation in 3.7% of the total 27 samples and no new case of tricuspid regurgitation was found from a total of 27 samples in this study shortly after the transcatheterization procesure. In a study conducted by Liu et al, (2013), it was found that the emergence of new cases of aortic valve regurgitation was 1.37% and tricuspid regurgitation was only around 0.57% of a total of 871 samples.…”
Section: Discussionmentioning
confidence: 48%
“…The reverse curve grants it pushability, control and fineness, in comparison to pigtail catheters which have a tendency to curl inside and can become difficult to manoeuvre and require more time in manipulation. Considering the fact that longer time spent manipulating catheters in the cardiac chamber is associated with arrhythmia [17] – both transient and life-threatening – SIM 1 catheter is ideal for a quick retrieval. The soft tip and ability to use the contralateral wall for support makes SIM 1 catheter a very useful device to hook IFB.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant arrhythmogenesis is not an uncommon complication during invasive coronary angiography, even though its incidence has declined nearly by half during the last decades (1.1% sVT/VF in 1960 vs. 0.6% in 1990). 1 The majority of these events is related to catheter and wire manipulations (direct myocardial stimulation, deep coronary intubation, superselective engagement etc) and can be prevented by optimizing the equipment and the technique such as preferring smaller size catheters with sideholes, avoid prolonged injections of large amount of contrast medium, or injections into the conus branch of the right coronary artery. 2 Whenever the aforementioned technical issues have been excluded as the cause of the arrhythmic event, the etiology can be attributed to myocardial toxicity of the contrast agent or underlying vulnerability of the patient due to electrolyte imbalance or QT prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant arrhythmogenesis is not an uncommon complication during invasive coronary angiography, even though its incidence has declined nearly by half during the last decades (1.1% sVT/VF in 1960 vs. 0.6% in 1990) 1 2 …”
Section: Discussionmentioning
confidence: 99%